Exploring the Benefits of Mind Sound Resonance Technique and its Ability to Improve the Quality of life – A Review Article - Hadke, Sonali; Penna, Madhusudan (International Research Journal of Ayurveda & Yoga, 2024)
The aim of this study is to evaluate the findings of selected articles regarding the effects of the Mind Sound Resonance Technique (MSRT) and to provide a comprehensive review of the benefits of the MSRT. Due to many things such as daily rush, work style, workload, goal fulfillment, increasing stress it creates mental and physical diseases. To prevent these diseases, it is necessary to inform everyone about the effect of MSRT and its benefits. Thus, this manuscript reports on a study of the effects of the MSRT on various group problems and situations. The MSRT is one of the many yoga techniques, which influences the Manomaya Kosha area of the Pancha Kosha. In this technique, use mantra to generate resonance in the body, which mainly works through the Manomaya Kosha to induce deeper relaxation for both mind and body. The results of this study show that practicing the MSRT improves mental health, reduces mental health symptoms, reduces burnout/fatigue, manages occupational stress, increases teacher importance, overcomes mental barriers, improves emotional regulation, and teacher–student relationships as well as increases cognitive performance, reduces anxiety and stress, improves sleep quality, improves mental health, regulates blood pressure, and helps reduce fatigue and pain. Of course, the MSRT works to enhance overall well-being and quality of life.